2011
DOI: 10.1099/vir.0.023010-0
|View full text |Cite
|
Sign up to set email alerts
|

High levels of HCV core+1 antibodies in HCV patients with hepatocellular carcinoma

Abstract: The core region of the hepatitis C virus (HCV) genome possesses an overlapping ORF that has been shown to encode a protein, known as the alternate reading frame protein (ARFP), F or core+1. The biological role of this protein remains elusive, as it appears to be non-essential for virus replication. However, a number of independent studies have shown that the ARFP/F/ core+1 protein elicits humoral and cellular immune responses in HCV-infected individuals and interacts with important cellular proteins. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
1
29
0
6
Order By: Relevance
“…Up to date, core+1/ARFP expression has been observed in in vitro translation systems and in transfected hepatoma cells. These studies revealed expression of the core+1/ARF ORF in subtypes 1a and 1b, either through ribosomal frameshift from the core frame at codons 8-11 (F form) (Xu et al, 2001;Varaklioti et al, 2002) or through internal translation initiation at core+1/ ARF ORF codons 85/87 (S form) (Vassilaki & Mavromara, 2003;Boumlic et al, 2011). Other core+1/ARFP isoforms have also been described (Boulant et al, 2003;Baril & Brakier-Gingras, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Up to date, core+1/ARFP expression has been observed in in vitro translation systems and in transfected hepatoma cells. These studies revealed expression of the core+1/ARF ORF in subtypes 1a and 1b, either through ribosomal frameshift from the core frame at codons 8-11 (F form) (Xu et al, 2001;Varaklioti et al, 2002) or through internal translation initiation at core+1/ ARF ORF codons 85/87 (S form) (Vassilaki & Mavromara, 2003;Boumlic et al, 2011). Other core+1/ARFP isoforms have also been described (Boulant et al, 2003;Baril & Brakier-Gingras, 2005).…”
mentioning
confidence: 99%
“…However, we recently observed core+1/ARFP expression in the JFH1-based bicistronic replicon system (unpublished results). Most importantly, indirect evidence, such as sequence analyses of HCV clinical isolates and higher prevalence of anti-core+1/ARFP antibodies in hepatocellular carcinoma (HCC) patients (Sobesky et al, 2007;Vassilaki & Mavromara, 2009;Dalagiorgou et al, 2011), implicates core+1/ARFP in liver cancer. Core protein has also been associated with HCC (Ahmad et al, 2011;Jahan et al, 2012) and, since the two ORFs overlap, core+1/ARFP may contribute to some of the functions attributed to the multifunctional core protein (Branch et al, 2005;Vassilaki & Mavromara, 2009).…”
mentioning
confidence: 99%
“…Responders were followedup for 6 months after termination of treatment and antibody titers were measured again at the week 72. Although 4 Jundishapur J Microbiol. In Press(In Press):e58294.…”
Section: Resultsmentioning
confidence: 99%
“…HCV is one of the leading causes of persistent infection in humans that can predispose to liver fibrosis and cirrhosis. There are some reports indicating that chronic hepatitis C (CHC) infection is strongly associated with hepatocellular carcinoma (HCC) (3)(4)(5)(6)(7)(8)(9). There is neither effective vaccine for immunization, nor a broadly effective treatment for HCV infection (3).Among different factors associated with chronic HCV infection, alternate reading frame protein (ARFP) or core+1 protein is one the newest ones that can promote persistent infection (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The F protein is localized in the endoplasmic reticulum (ER) region, implying that it has a role in viral morphogenesis (81). Previous work suggests that the F protein is expressed in natural HCV infections (16). B and T cell mediated immune responses specific to ARFP have been detected in HCV patients (4).…”
Section: Introductionmentioning
confidence: 98%